2018
DOI: 10.3390/scipharm86030036
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Anti-Proliferative Interaction of Flavonoid Quercetin and Toxic Metal Cadmium in the 1321N1 Human Astrocytoma Cell Line

Abstract: Cadmium (Cd) is a toxic heavy metal occurring in the environment as an industrial pollutant. The systematic accumulation of Cd in the human body may lead to major health problems. Quercetin (QE) is a natural flavonoid widely distributed in plants and is a part of human diet. Many studies have demonstrated the multiple benefits of QE to humans in protecting cells of our bodies. The aim of this study was to investigate the effect of QE and Cd on the proliferation of astrocytoma 1321N1 cells. Results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…Quercetin (Que) has been widely studied against many types of cancer cells, and its cytotoxic effect towards a number of murine and human brain cancer cell lines was also studied. Gliomas and glioblastomas, differing in their metastatic potential and/or drug resistance, were the most frequent cell lines used, with single papers describing the effect on astrocytoma [111][112][113] or neuroblastoma [114] cells. One study, by Lagerweij et al [115], was focused on medulloblastoma cell lines.…”
Section: Cytotoxicity and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin (Que) has been widely studied against many types of cancer cells, and its cytotoxic effect towards a number of murine and human brain cancer cell lines was also studied. Gliomas and glioblastomas, differing in their metastatic potential and/or drug resistance, were the most frequent cell lines used, with single papers describing the effect on astrocytoma [111][112][113] or neuroblastoma [114] cells. One study, by Lagerweij et al [115], was focused on medulloblastoma cell lines.…”
Section: Cytotoxicity and Mechanismsmentioning
confidence: 99%
“…A number of studies focused on evaluation of Que efficacy in combination with other approved drugs or other substances to verify the synergistic potential of the compound. Al-Hasawi et al [111] reported that combined exposure to Que and cadmium (200 µM and 16 µM, respectively) reduced viability of astrocytoma 1321N1 cells to 6.9%, in comparison to the incubation with each of the substances alone. The effect was significantly increased with longer incubation time (48 h).…”
Section: Synergismmentioning
confidence: 99%
“…After 24 h of incubation, the cells were then treated with different concentrations of compounds for 24 h. Next, 100 µL MTT solution at a concentration of 0.5 mg/mL was added to the cells, which were incubated at 37 • C for 4 h and then washed twice with PBS. Last of all, the prepared cells were lysed with 100 µL DMSO, and the absorbance was measured spectrophotometrically at 540 nm using an ELISA reader [27].…”
Section: Cell Viability Assay (Mtt Assay)mentioning
confidence: 99%
“…Flavonoids, including quercetin (3, 3, 4, 5, 7pentahydroxyflavone) (QE) are naturally occurring substances present virtually in all higher plants [1] and as such, they are present in human dietary components of a plant origin [2]. QE as a typical representative of this group of compounds was shown to possess significant therapeutic and protective biological properties, including antiaging, antiinflammatory, anti-diabetic, anti-obesity, angioprotective, and cytostatic [3,4]. QE has the potential to inhibit mTOR hyperactivity involved in cancer progression [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, QE possesses the potential of inhibiting kinases that are part of deregulation processes in malignantly transformed cells [7]. The effects of QE were reviewed in our previous work [4].…”
Section: Introductionmentioning
confidence: 99%